MO159CHA2DS2-VASC SCORE AS A PREDICTOR OF CARDIOVASCULAR MORTALITY IN CHRONIC KIDNEY DISEASE PATIENTS. (29th May 2021) - Vodošek Hojs, Nina; Ekart, Robert; Bevc, Sebastjan; Piko, Nejc; Hojs, Radovan
Abstract: Background and Aims: Cardiovascular mortality is high in chronic kidney disease (CKD) patients. Recognizing patients with higher cardiovascular risk might help in their treatment. CHA2 DS2 -VASc score was originally used to predict cerebral infarction in patients with atrial fibrillation (AF). However, it is also useful in predicting outcome in different cardiovascular conditions, independent of the presence of AF. Therefore, the aim of our research was to assess the role of CHA2 DS2 -VASc score in cardiovascular mortality in CKD patients. Method: Eighty-seven non-dialysis CKD patients from our outpatient clinic were included. At the time of inclusion, medical history data and standard blood results were collected and CHA2 DS2 -VASc score was calculated. Patients were followed for assigned time or until their death. Mean follow-up time was 1696.45±564.60 days. Results: Descriptive statistics of our patients are presented in table 1 . During follow-up 11 patients suffered from cardiovascular death. Univariate Cox regression analysis showed that CHA2 DS2 -VASc score is a significant predictor of cardiovascular mortality (HR: 2.19, CI: 1.42-3.37, p=0.001). In multivariate Cox regression analysis in which CHA2 DS2 -VASc score, serum creatinine, urinary albumin/creatinine, haemoglobin, high sensitivity CRP and intact PTH were included, CHA2 DS2 -VASc score was an independent predictor of cardiovascular mortality (HR: 2.04, CI: 1.20-3.45, p=0.008) (table 2 ). Conclusion: CHA2 DS2 -VASc score is a simple and quick way to identify cardiovascular risk in CKD patients.